Synthesis and characterization of Co3O4 nanoparticles for use as pigments in solar absorbing paints - Gardey Merino, María Celeste (2021)
This aim of this research is to produce Co3O4 oxide by means of one-step solution novel combustion methods usingaspatic acid (C4H7NO4); lysine (C6H14N2O2); tris (hydroximethyl) aminomethane (NH2C (CH2OH)3) and ethylene diaminetetra-acetic acid (C10H16N2O8) as fuels. The pigments were characterized using X-ray diffraction, scanning andtransmission electron microscopy, infrared spectroscopy with Fourier transform and UV-VIS-IR Spectrophotometry.The paint based on alkyd resin was made from pigments obtained (Co3O4 oxide). In order to make a comparison of thethermal emittance of the paint, two different formulations were prepared and these coating are named "absorbent paintcoating": one that included 1% by weight of aluminum in metallic powder and another, with 1% of copper in metallicpowder, respectively. The solar absorbance for the Co3O4 powders, plus quartz cuvette, gave a value of 0.9 in all cases.An extraordinary value of absorption on the coatings between 95 and 96% was noted. These results suggested that thesynthesis of combustion in solution makes it possible to obtain a Co3O4 absorbent pigment with different fuels.These syntheses have a low environmental impact because they are one-step processes. All use low amounts of reactiveash obtained at a calcination of about 500 °C. These results suggest the possibility of utilizing this oxide in absorbentsolar paints.